Relative bioequivalence evaluation of two oral atomoxetine hydrochloride capsules: a single dose, randomized, open-label, 2-period crossover study in healthy Chinese volunteers under fasting conditions - Shang, D-W; Guo, W; Zhou, F-C; Wang, X-P; Li, A-N; Zhang, L; Li, W-B; Lu, W; Wang, C-Y (Drug research (Stuttgart), 2013)
To evaluate the bioequivalence of a new formulation of atomoxetine hydrochloride (CAS 82248-59-7) capsules (test) and an available branded capsules (reference) after administration of a single 40 mg dose, randomized, open-label, 2-period crossover study was conducted in 22 healthy male Chinese subjects with a 1-week wash-out period. This study was designed for/the Honglin Pharmaceutical Co. Ltd and contracted to be done by the Beijing Anding Hospital in order to satisfy Chinese regulatory requirements to allow marketing of this generic product and performed according to the criteria of SFDA. Blood samples were collected before and 0.25, 0.5, 1, 1.5, 2, 3, 4, 6, 9, 12, 16 and 24 h after drug administration. Plasma concentrations were determined by high-performance liquid chromatography (HPLC) with UV detection. A non-compartmental method was used to calculate the pharmacokinetic parameters and evaluate bioequivalence of the 2 formulations. The 90% confidence interval (CI) of the ratios (test/reference) of atomoxetine for AUC0-24, AUC0-∞ and Cmax were 100.9% (93.6-108.8%), 103.1% (95.1-111.7%) and 105.2% (92.8-119.4%), respectively, which fell within the interval of 80-125% and 75-133%. No clinically significant changes or abnormalities were noted in laboratory data and vital signs. From these results it can be concluded that the test formulation of atomoxetine capsules met the regulatory criterion for bioequivalence to the reference formulation.